Energy efficiency assessment of technical school buildings : using the dynamic energy model and energy baseline estimation - Salma Mohamed Mohamed Hassan Elbahy; Ayman Hassaan (2022)
(3jgOa gPG GdHMK Edi Jbjje COGA GdWGbI aj eHfi GdJYdje hGdJOQjH Gdafj(B. (3YdGhI Ydi Pdc ,OQGSI CKQ COGA WGbI GdeHfi Ydi GdQVG GdLSOj ddWGdH hCOGFg GdCcGOjej(B. (3jJe JMbjb gPg GdCgOGa ef NdGd fhYjf ef GdWQb GdHMKjI(B: (3fXQjG hJLQjHkjG(B. (3ef GdfGMjI GdfXQjI , JVefJ GdOQGSI JLejkYG hefGbTI ddCOHjGJ PGJ GdUdI dJWhjQ eOQSI GdJYdje hGdJOQjH Gdafi hGdegfj , hJbjje COGA GdeHfi GdJYdjej(B. (3JLQjHkjG , jJe GSJNOGe JMdjd OQGSI GdMGdI eY GdebGHdGJ THg GdefXeI hGdJMdjd GdJaUjdj hGdJMdjd GdEMUGFj hfehPL GdeYGjQIs
Thesis (M.Sc.)-Cairo University - Faculty of Engineering - Department of Architectural Engineering
Bibliography: p. 171-179.
Keywords: Architectural Engineering; Workshops